On the pathogenesis of thromboses in antiphospholipid syndrome - T. A. Sukontseva; O. Yu. Kaplina (Акушерство, гинекология и репродукция)
Antiphospholipid antibodies (AFA) are a heterogeneous group of autoantibodies produced humans under various pathological conditions; the main one of those is the antiphospholipid syndrome. AFA cause a number of serious complications, such as thrombosis, pathology of pregnancy and childbirth, multisystem damage to organs and tissues. Thrombosis caused by AFA can develop both in the venous and arterial circulation, and are characterized by high mortality and morbidity rates.